Phyllodes tumor of the vulva: A case report and literature review highlighting a novel manifestation of Cowden syndrome - Sahana Somasegar; Lisa Han; Aaron Miller; Pankhuri Wanjari; Peng Wang; Jennifer A. Bennett; S. Diane Yamada (Elsevier, 2021)
Cowden syndrome is a rare hereditary cancer syndrome characterized by a germline PTEN mutation which results in an increased risk of developing breast, thyroid, and endometrial carcinoma, as well as widespread benign hamartomas. Phyllodes tumor (PT) is a rare fibroepithelial tumor that accounts for less than 1% of all breast tumors. As mammary-type glands can be found in the anogenital region, PTs can rarely arise in this location. We describe the presentation, workup and management of a PT of the vulva that developed in a patient with Cowden syndrome. This report represents the first time a vulvar PT has been described in association with Cowden syndrome and should be considered in the differential diagnosis of a slow-growing vulvar mass.